6(-2g-1)=-(113g+2)

Simple and best practice solution for 6(-2g-1)=-(113g+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(-2g-1)=-(113g+2) equation:



6(-2g-1)=-(113g+2)
We move all terms to the left:
6(-2g-1)-(-(113g+2))=0
We multiply parentheses
-12g-(-(113g+2))-6=0
We calculate terms in parentheses: -(-(113g+2)), so:
-(113g+2)
We get rid of parentheses
-113g-2
Back to the equation:
-(-113g-2)
We get rid of parentheses
-12g+113g+2-6=0
We add all the numbers together, and all the variables
101g-4=0
We move all terms containing g to the left, all other terms to the right
101g=4
g=4/101
g=4/101

See similar equations:

| 11/10x-1=-6 | | 59=17+6z | | 180-8x-22+6+2x+88=180 | | 22=-6u+4(u+2) | | 150(1-0.1)=n | | 15x+22(x-5)=186 | | 180-8x+22+6+2x+88=180 | | ​11/​3=​6/y | | -3x-3(5-4x)=4(x-5)-5 | | 7x+3+9x-9=180 | | 4x=1/2(x+56) | | 38=-3(y+4)-7y | | 5x-(3x-3)=2x+5 | | 2-14x-3+7x=-36 | | 50/b=25/33 | | -6p-5(2-+2p)=2(p-3)-10 | | 0=3/5g | | 5x+3x+7+2x=49-x+3x+14 | | -2/3f+1/5+3/5=0 | | |x-1|=-2 | | 7x+112=18x+18 | | ——3x-5=10 | | 2/3f-1/5+3/5=0 | | 8x+8=9x+8 | | 6+4(x+2)=6x | | 5-1/2n=12 | | 12n=-3 | | 5(v+4)=-6(-v+4) | | 3(x+5)=3x+11 | | -5x+7x-9=2(x-3)-6 | | 2x+3+x+4=180 | | -2(x-2)=5x-4 |

Equations solver categories